2016
DOI: 10.5812/ijp.5212
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Risk Factors and Follow-Up Criteria for Severity of Snakebite in Children

Abstract: BackgroundSnakebites are an emergency medical condition and require rapid treatment procedures in children.ObjectivesThis study aimed to present an overview of the demographic characteristics, clinical presentations, laboratory findings, severity, and complications that developed in pediatric patients due to snakebites.Patients and MethodsA total of 151 children with snakebite were enrolled in the study. All patients had a history of snakebite obtained between June 2006 and August 2015 retrospectively.ResultsD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
5
0
5
Order By: Relevance
“…WBC and AST/ALT ratio can be used as follow-up criteria in children with snakebite. 1 The present study indicated that MPV, NLR and PLR may be useful for the diagnosis as inflammatory markers of snakebite. To our knowledge, this is the first study investigating the relationship between snakebite and serum complete blood count parameters in children.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…WBC and AST/ALT ratio can be used as follow-up criteria in children with snakebite. 1 The present study indicated that MPV, NLR and PLR may be useful for the diagnosis as inflammatory markers of snakebite. To our knowledge, this is the first study investigating the relationship between snakebite and serum complete blood count parameters in children.…”
Section: Discussionmentioning
confidence: 93%
“…[1][2][3] Therefore, precise diagnosis of snakebite envenomation requires accurate identification of the snakebite and investigation of the clinical findings of envenomation. 3 The laboratory signs of envenomation are derived from the severe cytotoxic, hematopoietic system and inflammatory effects of the venom.…”
Section: Introductionmentioning
confidence: 99%
“…El recuento de leucocitos y el índice de AST-ALT pueden usarse como criterios de seguimiento de los niños con mordedura de serpiente. 1 Según el estudio actual, el VPM, el INL y el ITL podrían servir para el diagnóstico como marcadores inflamatorios de la mordedura de serpiente. Hasta donde sabemos, este es el primer estudio que investigó la relación entre la mordedura de serpiente y los parámetros séricos del hemograma completo en niños.…”
Section: Discussionunclassified
“…[1][2][3] Por lo tanto, el diagnóstico preciso de intoxicación por mordedura de serpiente requiere la identificación precisa de la mordedura de serpiente y el estudio de los datos clínicos relativos a la intoxicación por mordedura de ofidio venenoso. 3 Los datos de laboratorio de la intoxicación por mordedura de ofidio venenoso se obtienen a partir de los graves efectos del veneno a nivel citotóxico, inflamatorio y del sistema hematopoyético.…”
Section: Introductionunclassified
“…Literature shows that 28% had required fasciotomy among a study population of 90 subjects with snake envenomation. (15) Swelling of envenomed muscle within such tight fascial compartments could result in an increase in tissue pressure above the venous pressure and result in ischaemia. However, the classical signs of an intracompartmental pressure syndrome may be difficult to assess in snakebite victims.…”
Section: Discussionmentioning
confidence: 99%